Student Satisfaction at Higher Education Institutions in Turkey: A Case of Faculty of Education - Şakir Çınkır; Sevgi Yıldız (Anı Publishing, 2019)
This study aims to explore the satisfaction of students studying at university with the education and learning, examination and support services they receive. The study group of the research is comprised of 500 students in total studying in eight programs at five faculties of education in Turkey. Research data was collected using a data collection instrument developed by the researchers and focusing on the critical incidents based on student experiences. Data acquired from the students was subjected to content analysis through NVivo program. According to the research findings, student experiences in attitude, functionality and proficiency themes, respectively, were found to be critical in their satisfaction with education-learning, exams, and support services. Also, while experiences in socializing, communication and access themes enable students to feel satisfied with these services, experiences in management, safety, and payment themes were found to be the sources of dissatisfaction. According to these results, higher education institutions are recommended to do improvement and development activities by reviewing their policies based on the results derived from the satisfaction research.